1998
DOI: 10.1159/000022027
|View full text |Cite
|
Sign up to set email alerts
|

Memory Awareness in Nursing Home Residents

Abstract: Background: Health care providers often believe that individuals with cognitive disturbance are unaware of their deficits. The term unawareness was first used to describe hemiplegia following right hemisphere stroke but has since been applied to unawareness of any neurological or neuropsychological deficit. Clinicians usually rely on their subjective observations to evaluate the patient’s awareness of deficits, and few investigators have systematically evaluated this important clinical phenomenon. Objective: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Cognitive function was assessed using the MMSE, a brief, widely used, and easily administered 20-item test of cognitive function, including orientation, registration, language and praxis, memory recall, and attention/calculation ability. Scores range from 0-30, with scores of 23 and below typically indicative of cognitive impairment (Karuza, Katz, & Henderson, 1997;McDougall, 1998;Phillips, Chu, Morris, & Hawes, 1993). (Ware & Sherbourne, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…Cognitive function was assessed using the MMSE, a brief, widely used, and easily administered 20-item test of cognitive function, including orientation, registration, language and praxis, memory recall, and attention/calculation ability. Scores range from 0-30, with scores of 23 and below typically indicative of cognitive impairment (Karuza, Katz, & Henderson, 1997;McDougall, 1998;Phillips, Chu, Morris, & Hawes, 1993). (Ware & Sherbourne, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…Kuder-Richarson's estimate of reliability for scores on the GDS was 0.78. Because research has demonstrated that mood affects not only cognitive functioning but also self-confidence, we hypothesized that scores on the MMQ would be positively correlated with scores on the GDS (Ide, McDougall, & Wykle, 1999;McDougall, 1998). Fort's (2000) Memory Aging Questionnaire (MAQ) was administered to assess how participants conceived of memory changes with advancing age.…”
Section: Methodsmentioning
confidence: 99%
“…In one study healthy older males had lower scores on selfreported memory function than females (McDougall, 1998a). In another study of nursing home residents, McDougall (1998b) found scores on the capacity and change metamemory scales were significantly lower in the group with mixed depression and cognitive impairment when compared to a group with cognitive impairment and no depression. This phenomenon of compromised thinking, anxiety, and decreased confidence in memory has been described as mental frailty by McDougall and Balyer (1998) and sense of control by Lachman, Steinberg, and Trotter (1987) and Lachman and Leff (1989).…”
mentioning
confidence: 94%